Students’ problem solving ability in thinking aloud pair problem solving learning assisted by schoology viewed from mathematical disposition - Winarti, Endang Retno; Haryanti, Monika Dwi; Asih, Tri Sri Noor (Unnes Journal of Mathematics Education, 2019)
This research aimed to determine whether Thinking Aloud Pair Problem Solving learning assisted by Schoology was effective to problem solving ability. The method of this research was quantitative-assisted interviews. This research involved 63 selected students of 252 of 8th grade students in one of junior high schools in Kudus. The results showed that: (1) students' problem solving ability in Thinking Aloud Pair Problem Solving learning assisted by Schoology achieved the mastery learning; (2) students’ problem solving ability who received Thinking Aloud Pair Problem Solving learning assisted by Schoology was better than students who received Problem Based Learning; and (3) mathematical disposition possitively affected to the students’ problem solving ability.